Cross-sectional and prospective relationship between physical activity and chronic diseases in European older adults - Marques, Adilson (2017)
Objectives This study examined the relationship between physical activity (PA) and chronic diseases in European older adults, using a prospective analysis with data from 2011 and 2013. Methods Participants were 37,524 older adults (16,204 men) who responded to the fourth (in 2011) and fifth (in 2013) wave of SHARE project, from 13 European countries. Participants’ answers to interview questions about the presence of chronic conditions and PA. The cross-sectional and prospective association between PA and the number of chronic diseases was assessed using general linear models. Results Among men and women, moderate or vigorous physical activity (MVPA) in 2011 was associated with fewer reported chronic diseases in 2011 and 2013. In prospective analysis, MVPA in 2011 was inversely associated with the number of chronic diseases in 2013 in the unadjusted model. In the adjusted model MVPA more than once a week remained as a significant predictor of fewer chronic diseases. Conclusions PA should be prescribed to older adults in order to prevent and reduce the number of chronic diseases, and, when possible, vigorous intensity PA should be recommended.